Predicting New Product Success or Failure:: A Comparison of U.S. and U.K. Practices - Berkowitz, David; Wren, Brent; Grant, E. (Journal of Comparative International Management)

(untitled) (Management Futures, 2007)
We propose a model that allows managers to assess new product development (NPD) projects, combined with the anticipated strategy, prior to introduction and to estimate a probability of success. This model allows for an evaluation and prioritization of resource commitments. A test of this model that compares companies within the United States (U.S.) and the United Kingdom (U.K.) is provided.